2005
DOI: 10.7863/jum.2005.24.9.1235
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Comparison of Ultrasonic Backscatter Coefficient Measurements From 2 to 9 MHz

Abstract: Objective. As are the attenuation coefficient and sound speed, the backscatter coefficient is a fundamental ultrasonic property that has been used to characterize many tissues. Unfortunately, there is currently far less standardization for the ultrasonic backscatter measurement than for the other two, as evidenced by a previous American Institute of Ultrasound in Medicine (AIUM)-sponsored interlaboratory comparison of ultrasonic backscatter, attenuation, and speed measurements (J Ultrasound Med 1999; 18:615-63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 44 publications
3
119
0
Order By: Relevance
“…The authors postulated that they would have benefited from the use of a common reference material. Wear et al (2005) observed a large range of variation, of up to two orders, in absolute magnitude of backscatter coefficient measured at the different centres.…”
Section: Quality Assurance and Calibrationmentioning
confidence: 87%
See 2 more Smart Citations
“…The authors postulated that they would have benefited from the use of a common reference material. Wear et al (2005) observed a large range of variation, of up to two orders, in absolute magnitude of backscatter coefficient measured at the different centres.…”
Section: Quality Assurance and Calibrationmentioning
confidence: 87%
“…A contemporary agar-based TMM has been designed and established as part of an International Electrotechnical Commission project (IEC 2001;Teirlinck, Bezemer, Kollmann, Lubbers, Hoskins, Fish, Fredfeldt, & Schaarschmidt 1998). This has found uses in a range of medical ultrasound research projects (Madsen et al 2005;Meagher et al 2007;Poepping et al 2002;Ramnarine, Kanber, & Panerai 2004). It has also been utilised at the Barts and the London NHS Trust to develop test objects investigating the feasibility of high frequency ultrasound transducers (Carey et al 2004) based on the fluoropolymer PVdF (polyvinylidene difluoride, also known as KYNAR®).…”
Section: Tissue Mimicking Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic properties of the materials are given in Table 1. The propagation speeds and attenuation coefficients were measured by the method of [15], and the backscatter coefficients by [16].…”
Section: Ultrasound Phantommentioning
confidence: 99%
“…[7][8][9] These studies have enabled researchers to uncover sources of errors in measurements that, once eliminated, resulted in inter-laboratory agreement among BSC estimates on identical samples. 8,9 The studies by Wear et al, 7 Anderson et al, 8 and King et al 9 focused on laboratory-based systems, measurement, and data processing techniques. However, to apply QUS in a clinical setting, it is necessary to also demonstrate system and operator independence of BSC estimates using arraybased ultrasound imaging systems.…”
Section: Introductionmentioning
confidence: 99%